Embedding social inclusiveness and appropriateness in engineering assessment of green infrastructure to enhance urban resilience. Issue 1 (2nd January 2019) - Ward, Sarah; Staddon, Chad; De Vito, Laura; Zuniga-Teran, Adriana; Gerlak, Andrea K.; Schoeman, Yolandi; Hart, Aimee; Booth, Giles
ABSTRACT: Urban resilience emerges not only from 'what' is done in relation to critical infrastructure systems, but in the 'how' of their conception, co-creation and integration into complex socio-ecological-technical systems. For green infrastructure, where ownership and agency may be distributed amongst organisations and diverse communities, inclusiveness and appropriateness require embedding in engineering assessments of green infrastructure and resilience. Through consideration of past, present and future engineering and resilience assessments – from monetising, through greening, to humanising – this paper examines the ways in which GI may be or has already contributed to enhancing urban resilience and types of assessment and indicators that have been or could be used. We suggest that enhancing visibility of the 'whos' (individuals, communities) is crucial to fully diversifying assessments. We also suggest some ideas for additional indicators and assert that co-production of future indicators needs to be undertaken with appropriate professionals (e.g. social impact assessment professionals).